In vitro renal toxicity and in vivo therapeutic efficacy in experimental murine cryptococcosis of amphotericin B (Fungizone) associated with Intralipid. - Joly, V (1994)
We compared the experimental toxicities and activities of deoxycholate amphotericin B (d-AmB) dissolved in glucose (Dd-AmB) or mixed with 20% Intralipid (ILd-AmB). In vitro, ILd-AmB against renal tubular cells in primary culture. In vivo, the toxicities and activities of Dd-AmB and ILd-AmB were studied in DBA2 mice with cryptococcosis. The maximum tolerated dose of intravenously administered d-AmB, i.e., the dose that induced less than 15% mortality because of toxicity, was 1.7 to 2.5 times higher when it was administered as ILd-AmB than when it was administered as Dd-AmB. Both treatments given intravenously at the same dose were equivalent for improving the survival of mice and reducing CFU counts in infected tissue, but at maximum tolerated doses, ILd-AmB (2 mg/kg of body weight) was more effective than Dd-AmB (0.8 to 1.2 mg/kg). AmB concentrations in spleen, liver, lung, and kidney were measured by high-pressure liquid chromatography 4 and 24 h after a single injection of 1.2 mg of Dd-AmB per kg, 1.2 mg of ILd-AmB per kg, or 2 mg of ILd-AmB per kg. In a given organ, AmB levels were similar after administration of 1.2 mg of Dd-AmB or ILd-AmB per kg but were significantly higher after administration of 2 mg of ILd-AmB per kg. The lower level of toxicity of ILd-AmB might be explained by circular dichroism experiments, showing that ILd-AmB contained 10-fold less soluble oligomeric AmB, which is believed to be the toxic form of the drug, than Dd-AmB. We conclude that ILd-AmB is as efficient as Dd-AmB and is better tolerated than Dd-AmB in mice with experimental cryptococcosis. By allowing higher doses of AmB to be infused, Intralipid enhances AmB concentrations in infected sites, and thus the therapeutic activity of the drug.